2017
DOI: 10.1136/sextrans-2016-052961
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of costs of single and dual rapid HIV and syphilis diagnostics: results from a randomised controlled trial in Colombia

Abstract: BackgroundHIV and congenital syphilis are major public health burdens contributing to substantial perinatal morbidity and mortality globally. Although studies have reported on the costs and cost-effectiveness of rapid diagnostic tests (RDTs) for syphilis screening within antenatal care in a number of resource-constrained settings, empirical evidence on country-specific cost and estimates of single RDTs compared with dual RDTs for HIV and syphilis are limited.MethodsA cluster randomised controlled study design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 12 publications
(9 reference statements)
0
26
0
1
Order By: Relevance
“…3234,43,44 The impact of antenatal RST in increasing uptake and treatment rates has also been highlighted in some studies. 37,7073 Although the review has shown the inclusion of molecular techniques, which are more sensitive, for example, for early diagnosis of HIV infection in infants 41,42 and for screening for malaria in pregnant women, 86 there is still a need for high-quality assays in remote and rural primary care settings. The review also found varied performance of HRP2 RDT, particularly for asymptomatic malaria, which can still be used although it would miss some malaria cases.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3234,43,44 The impact of antenatal RST in increasing uptake and treatment rates has also been highlighted in some studies. 37,7073 Although the review has shown the inclusion of molecular techniques, which are more sensitive, for example, for early diagnosis of HIV infection in infants 41,42 and for screening for malaria in pregnant women, 86 there is still a need for high-quality assays in remote and rural primary care settings. The review also found varied performance of HRP2 RDT, particularly for asymptomatic malaria, which can still be used although it would miss some malaria cases.…”
Section: Discussionmentioning
confidence: 99%
“…37 The study also found that the costs for dual testing for HIV/syphilis and treatment for syphilis are high. 37 Dual HIV/syphilis testing represents an important opportunity for PMTCT of HIV and syphilis.…”
Section: Availability Of Poc Testing For Pmtct In Lmicsmentioning
confidence: 92%
See 3 more Smart Citations